MEDICINES: Expireds’ discart and utilization of leftovers - Pereira, Marlucia Beatriz Lopes (2018)
Storage and improper medicines’ discart causes damage to health. Had as objetive evaluate the medicines’ discart by families attended at Basic Health Unit of North Minas. Descriptive, quantitative and transversal study. In research’s field, data were collected by semistructured questionnaire. The results were: 82% stored medicines at home being the locals: bedroom, kitchen, bathroom. 68% of respondents watched the appearance and validity of the medication when used.In relation to the discart of leftovers, 51% deposit in commom trash or in the sewage and after the validate this number increases to 86%, while 13% report not discart 76% believe that improper discart causes public health problems and 82% says that were not oriented about correct practice. According to exposed above notes a worrying number of medicines stored at home, improves discart and disinformation. Therefore needs to planning strategies in public Health to minimize this situation.